Impact of free curcumin and curcumin nanocapsules on viability and oxidative status of neural cell lines - Bissacotti B.F. (2023)
© 2021 Informa UK Limited, trading as Taylor & Francis Group.Curcumin is an active polyphenol substance found in the highest concentrations in the roots of Curcuma longa. Its health benefits have led to recent increases in the consumption of curcumin. It has anti-inflammatory and antioxidant activities and is a potent neuroprotective against diseases of the brain. Nevertheless, its low bioavailability and its relative difficulty crossing the blood-brain barrier limit curcumin’s use for these purposes. Curcumin-loaded nanoparticles may be an effective treatment for several diseases although there is a paucity of studies reporting its safety in the central nervous system (CNS). Therefore, this study aimed to identify non-neurotoxic concentrations of free curcumin and two nanoformulations of curcumin. Cell lines BV-2 and SH-SY5Y, both originating from the CNS, were evaluated after 24, 48, and 72 h of treatment with free curcumin and nanocapsules We measured viability, proliferation, and dsDNA levels. We measured levels of reactive oxygen species and nitric oxide as proxies for oxidative stress in culture supernatants. We found that free curcumin was toxic at 10 and 20 µM, principally at 72 h. Nanoformulations were more neurotoxic than the free form. Safe concentrations of free curcumin are between 1–5 µM, and these concentrations were lower for nanoformulations. We determined the ideal concentrations of free curcumin and nanocapsules serving as a basis for studies of injuries that affect the CNS.